MINERAL MATTER IN COAL - Susilawati, Rita (Buletin Sumber Daya Geologi, 2015)
The term âmineral matterâ in coal is defined as all inorganic, non-combustible material that is in or associated with coal which include discrete crystalline mineral particles, dissolved ions and other inorganic components in the pore water or surface water of the coal, and inorganic elements combined within the organic compounds of the coal macerals. The minerals existing in coal are aresult of processes that occur throughout the entire history of coal formation. Its distribution is influenced by biological, hydrological and geochemical factors. Quartz and the clay minerals are the most widespread and abundant mineral found in coal. Another common minerals are feldspars and carbonate in the form of siderite, calcite and dolomite and sulfide minerals such as pyrite. Coal mineral matter analysis and characterization are useful for various reasons, particularly to take as much as benefit from coal utilization and to avoid any negative influence of coal inorganic components to the environment.